Sanitation-hygiene Knowledge, Practices and Human Health Impacts: Insights from Coastal Bangladesh - Md. Shohel Khan; Shitangsu Kumar Paul (Department of Geography Education, University of Jember, 2023)
Better sanitation and hygiene are very significant for sound health for human lives and it protects various water borne disease. This study aims to find sanitation-hygiene knowledge, practices and impacts on human health of coastal Bangladesh. Rajoir (Sarankhola), Gangarampur (Batiaghata) and Ganapatipur (Kalaroa) villages are purposively designated from shoreline, interim and inland coast. Data are collected with semi-structured questionnaire between July-October 2022 and analyzed through SPSS and map is produced with Arc GIS. Overall about 9.6, 36.3 and 54.1% respondents have good, moderate and poor knowledge regarding sanitation and hygiene. Overall about 57% respondents have accessed sanitary latrines. About 67% respondents claimed that their children deface are thrown in the toilet, followed by, around the house (16%). About 70, 83 and 84% respondents wash their hands with soap/handwash after defecation in shoreline, interim and inland area, followed by, 34, 35 and 27% before taking meal; 19, 19 and 4% before cooking; 9, 21 and 16% after household chores. Cleanliness index are categorized into satisfactory levels except water containers for shoreline (0.677) and inland (0.718) areas. About 96% (shoreline), 91% (interim) and 95% (inland) respondents claim women play a direct role during collection of water. Based on sanitation inspection tool, overall 6, 41, 47 and 3% tube-wells are grouped into very high, high, intermediate and low risk categories. About 57% (shoreline), 48% (interim) and 36% (inland) water sources are grouped into ‘high’s category. The study suggest to formate management committee to monitor proper sanitation and hygiene systems. Keywords : Coastal area; human health; cleanliness; sanitary inspection tool Copyright (c) 2023 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License